Celastrol ameliorates Cd‐induced neuronal apoptosis by targeting NOX2‐derived ROS‐dependent PP5‐JNK signaling pathway. Issue 1 (24th February 2017) - Xu, Chong; Wang, Xiaoxue; Gu, Chenjian; Zhang, Hai; Zhang, Ruijie; Dong, Xiaoqing; Liu, Chunxiao; Hu, Xiaoyu; Ji, Xiang; Huang, Shile; Chen, Long
Abstract: Celastrol, a plant‐derived triterpene, has neuroprotective benefit in the models of neurodegenerative disorders that are characterized by overproduction of reactive oxygen species (ROS). Recently, we have reported that cadmium (Cd) activates c‐Jun N‐terminal kinase (JNK) pathway leading to neuronal cell death by inducing ROS inactivation of protein phosphatase 5 (PP5), and celastrol prevents Cd‐activated JNK pathway against neuronal apoptosis. Therefore, we hypothesized that celastrol could hinder Cd induction of ROS‐dependent PP5‐JNK signaling pathway from apoptosis in neuronal cells. Here, we show that celastrol attenuated Cd‐induced expression of NADPH oxidase 2 (NOX2) and its regulatory proteins (p22 phox, p40 phox, p47 phox, p67 phox, and Rac1), as well as the generation of ROS in PC12 cells and primary neurons. Also, N ‐acetyl‐l ‐cysteine, a ROS scavenger, potentiated celastrol's inhibition of the events in the cells triggered by Cd, implying neuroprotection by celastrol via blocking Cd‐evoked NOX2‐derived ROS. Further research revealed that celastrol was involved in the regulation of PP5 inactivation and JNK/c‐Jun activation induced by Cd, as celastrol prevented Cd from reducing PP5 expression, and over‐expression of wild‐type PP5 or dominant negative c‐Jun strengthened celastrol's inhibition of Cd‐induced phosphorylation of JNK and/or c‐Jun, as well as apoptosis in neuronal cells. Of importance, inhibiting NOX2 with apocynin or silencing NOX2 by RNA interference enhanced the inhibitory effects of celastrol on Cd‐induced inactivation of PP5, activation of JNK/c‐Jun, ROS, and apoptosis in the cells. Furthermore, we noticed that expression of wild‐type PP5 or dominant negative c‐Jun, or pretreatment with JNK inhibitor SP600125 reinforced celastrol's suppression of Cd‐induced NOX2 and its regulatory proteins, and consequential ROS in neuronal cells. These findings indicate that celastrol ameliorates Cd‐induced neuronal apoptosis via targeting NOX2‐derived ROS‐dependent PP5‐JNK signaling pathway. Our data highlight a beneficial role of celastrol in the prevention of Cd‐induced oxidative stress and neurodegenerative diseases. Abstract : We propose that celastrol, a plant‐derived triterpene, ameliorates cadmium (Cd)‐elicited neuronal apoptosis by preventing Cd from upregulating reactive oxygen species (ROS)‐generating NOX2 and its regulatory proteins (p22phox, p40phox, p47phox, p67phox, and Rac1), thus suppressing ROS inactivation of PP5 and activation of JNK pathway. The findings highlight a beneficial role of celastrol in the prevention of Cd‐induced oxidative stress and neurodegenerative diseases.